Consumer engagement with social media platforms: A study of the influence of attitudinal components on cutting edge technology adaptation behaviour. (August 2021) - Muhammad, Syed Sardar; Dey, Bidit L.; Kamal, Muhammad M.; Syed Alwi, Sharifah F.
Abstract: Despite pervasive use of digital devices, the influence of simultaneous and combined attitudinal components on consumers' social media adaptation behaviours remains understudied. This research aims to address this gap in the literature by examining the influence of combined attitudinal components on consumers' continuous interaction with social media platforms. An online survey was conducted to obtain robust quantitative data on consumers' interaction and engagement with cutting edge technology such as social media. The findings indicate that consumers' combined cognitive (perceived opportunity, perceived social influence and perceived control) and affective (enjoyment, self-enhancement, trust and fear) attitudinal components are the antecedents to consumers' positive and negative adaptation behaviours of social media platforms. Consumers continuously engage with cutting edge social media platforms, either in positive adaptation behaviour (exploration to maximise or exploitation to satisfice social media led benefits) or negative adaptation behaviour (explore to revert from or avoid social media platforms) influenced by combined cognitive and affective attitudinal attributes. The study enriches and advances existing literature by identifying and analysing the influence of both cognitive and affective attitudinal attributes influencing consumers' positive and negative adaptation behaviours of cutting edge digital technology such as social media platforms. The study helps marketers and IS managers in profiling consumers and understanding consumption patterns while interacting with cutting edge social medial platforms. Highlights: Cognitive and affective attitudinal attributes influencing consumers' positive and negative adaptation behaviours Consumers continuously engage with cutting edge platforms in positive or negative adaptation behaviours. Consumers' affective attitude needs to be studied as antecedents to their adaptation behaviour.